Cross-listing, bonding hypothesis and corporate governance - Charitou, Andreas; Louca, Christodoulos; Panayides, Stelios (My University, 2007)
This paper examines the relationship between cross-listing and corporate governance for Canadian firms, that were cross-listed on US stock exchanges during the period 1997-2003. We find that cross-listed firms have more independent boards and audit committees after the listing relative to a non-cross-listed matched sample of firms and relative to the pre-listing period. Moreover, cross-listed firms experience changes in their ownership structure after the listing. Finally, we provide evidence that the sensitivity of the relation between cross-listed firm valuation with audit committee independence and ownership structure becomes more important after the listing. The results are robust after adjusting for various firm risk characteristics. Overall, the results are consistent with the literature on the bonding role of cross-listings on US stock exchanges.
Keywords: Bonding hypothesis; Corporate governance; Cross-listing